2013
DOI: 10.1128/aem.01873-12
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Reductive Dehalogenases by Using Blue Native Polyacrylamide Gel Electrophoresis

Abstract: f Dehalococcoides mccartyi strains are obligate organohalide-respiring bacteria harboring multiple distinct reductive dehalogenase (RDase) genes within their genomes. A major challenge is to identify substrates for the enzymes encoded by these RDase genes. We demonstrate an approach that involves blue native polyacrylamide gel electrophoresis (BN-PAGE) followed by enzyme activity assays with gel slices and subsequent identification of proteins in gel slices using liquid chromatography coupled to tandem mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(100 citation statements)
references
References 34 publications
2
98
0
Order By: Relevance
“…Additionally, HupL (DET0110) appeared in lower bands, suggesting that DET0110 and DET0112 do not comigrate. This finding is supported by a previous investigation that used blue native PAGE (BN-PAGE) gels to separate RDases from the D. mccartyi-containing KB-1 consortia in order to monitor reductive dechlorination activity (43). For the TCE-induced consortia in that study, proteomic sequencing of the active band identified homologs of DET0187 and DET0186 with the KB1 homolog of DET0112.…”
Section: Genomic Differences Betweensupporting
confidence: 71%
See 2 more Smart Citations
“…Additionally, HupL (DET0110) appeared in lower bands, suggesting that DET0110 and DET0112 do not comigrate. This finding is supported by a previous investigation that used blue native PAGE (BN-PAGE) gels to separate RDases from the D. mccartyi-containing KB-1 consortia in order to monitor reductive dechlorination activity (43). For the TCE-induced consortia in that study, proteomic sequencing of the active band identified homologs of DET0187 and DET0186 with the KB1 homolog of DET0112.…”
Section: Genomic Differences Betweensupporting
confidence: 71%
“…Blue native gel separations were performed by previously published methods (43). In brief, a stable pool of proteins was established by growing a 5-liter culture derived from the D2 mixed community at a continuous respiration rate of 2.5 M Cl Ϫ /h for 800 h. The culture was centrifuged and was frozen at Ϫ80°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blue Native PAGE is a promising approach for examining in vitro reductive dehalogenase activity [76,81]. The current frontier of biochemical research on the reductive dehalogenases involves attempts to heterologously express reductive dehalogenase encoding genes and to engineer an OHRB with desirable substrate preferences.…”
Section: Dehalococcoides Mccartyi Dehalococcoides Mccartyi Cbdb1 Cbdb1mentioning
confidence: 99%
“…The function of TCE RDase, TceA, in transforming TCE to ethene has also been identified [61]. VcrA and BvcA catalyze the transformation of DCE to ethene [62,63]. In addition to chloroethenes, RDases also could reduce other chlorinated compounds.…”
Section: Degradation Enzymesmentioning
confidence: 99%